The Urgency of Maqashid Al-Sharia in Everyday Life - Dasrizal, Dasrizal; Rusli Zarkasyi, Ramzy; Arfen Azizah, Isnel; Maulida Hania; Junaidi, Junaidi; Nurliana, Nurliana (Jurnal Elsyakhshi, 2024)
Maqashid sharia has an important role in the lives of Muslims by emphasizing on five main aspects, namely ad-din (religion), an-nafs (soul), an-nasab (offspring), al-aql (reason), and al-mal (property). This research aims to create benefits and protect basic human interests, so that justice in society can be realized. This research uses a qualitative method with a literature approach. Data collection techniques are carried out through review and analysis of various related literature. The data obtained were analyzed using content analysis techniques with a deductive-inductive approach. The results showed that the implementation of maqashid sharia has significant urgency in realizing the benefits of Muslims in various aspects of life, including social, economic, educational, and interpersonal relationships. The application of this concept plays a role in creating a just, harmonious, peaceful society in accordance with the principles of Islamic sharia.